2017
DOI: 10.1007/s40292-017-0229-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns, Nutrition Knowledge, Lifestyle, and Health-Related Quality of Life: Associations with Anti-Hypertension Medication Adherence in a Sample of Australian Adults

Abstract: A healthier dietary pattern, better exercise self-efficacy and adequate sleep (more than six hours a night) may increase the likelihood of AHT adherence in individuals with high BP. Interventions focusing on improving these variables are required to confirm the findings of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…In this study, sleep disorders were associated with medication nonadherence; insomnia, in particular, significantly increased the likelihood of reducing the medication dose. This is consistent with the results of previous studies [ 19 , 20 ]. Additionally, we found that using dietary supplements was associated with a 4.82-fold increase in the risk of discontinuing medication, compared with not using dietary supplements, which is in line with the results from previous studies showing that hypertensive patients who use complementary and alternative therapies have low adherence to antihypertensive medication [ 11 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, sleep disorders were associated with medication nonadherence; insomnia, in particular, significantly increased the likelihood of reducing the medication dose. This is consistent with the results of previous studies [ 19 , 20 ]. Additionally, we found that using dietary supplements was associated with a 4.82-fold increase in the risk of discontinuing medication, compared with not using dietary supplements, which is in line with the results from previous studies showing that hypertensive patients who use complementary and alternative therapies have low adherence to antihypertensive medication [ 11 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, wellbeing assessment needs to be adapted to the population heterogeneity, with comorbidity as a keystone in the medical field [17]. Lifestyle adequation to some standards is known to be related to a higher health-related quality of life [4,[20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…The internal consistency of self-efficacy questionnaires was good with alpha levels of 0.76 and 0.89, for self-efficacy of diet (with 8 questions) and self-efficacy of exercise (with 4 question), respectively. A fouritem questionnaire developed for this study and described before [26] was used for assessing AHT adherence. Answers were scored on a 3-point scale.…”
Section: Design and Data Collectionmentioning
confidence: 99%